Perencanaan Ulang Tata Letak Fasilitas Produksi (Studi Kasus: UKM Pengolahan Ikan Asin Stefen Aluy-Meulaboh) - Hadi, Khairul; Hasanuddin, Iskandar; Husni, Husni; Pamungkas, Iing; Fitriadi, Fitriadi; Irawan, Heri Tri (Universitas Teuku Umar, 2020)
This study used a rectilinear method in redesigning the layout of the salted fish production facility to minimize the mileage of Stefen Aluy's UKM. Stefen Aluy UKM is one of the salted fish businesses that is developing in West Aceh and its products are evenly distributed in West Aceh and its surroundings. The large production area makes it easier for UKM Stefen Aluy to maximize salted fish production. However, the large production area owned by UKM Stefen Aluy can result in long distances so that it is ineffective and efficient. The risk of worker fatigue and injury can occur due to the long distance. In addition, there is a risk of raw materials falling while moving. To minimize this potential, it is necessary to evaluate the layout of the salted fish production facilities at UKM Stefen Aluy, namely by improving the layout of the facilities. The rectilinear method can be used to minimize mileage in making layout improvements. From the results of the layout mapping based on the measurement of the rectilinear distance, the initial layout has a rectilinear distance of 6.932 cm, while the layout of the design results obtained a rectilinear distance of 3.409 cm. The result of the layout redesign resulted in a distance reduction of 49.04% from the previous distance.